An optimized protocol for assessment of sputum macrorheology in health and muco-obstructive lung disease - Völler, Mirjam; Addante, Annalisa; Rulff, Hanna; von Lospichl, Benjamin; Gräber, Simon Y.; Duerr, Julia; Lauster, Daniel; Haag, Rainer; Gradzielski, Michael; Mall, Marcus A. (Frontiers in Physiology, 2022)
Background: Airway mucus provides important protective functions in health and abnormal viscoelasticity is a hallmark of muco-obstructive lung diseases such as cystic fibrosis (CF). However, previous studies of sputum macrorheology from healthy individuals and patients with CF using different experimental protocols yielded in part discrepant results and data on a systematic assessment across measurement settings and conditions remain limited. Objectives: The aim of this study was to develop an optimized and reliable protocol for standardized macrorheological measurements of airway mucus model systems and native human sputum from healthy individuals and patients with muco-obstructive lung disease. Methods: Oscillatory rheological shear measurements were performed using bovine submaxillary mucin (BSM) at different concentrations (2% and 10% solids) and sputum samples from healthy controls (n = 10) and patients with CF (n = 10). Viscoelastic properties were determined by amplitude and frequency sweeps at 25 °C and 37 °C with or without solvent trap using a cone-plate geometry. Results: Under saturated atmosphere, we did not observe any temperature-dependent differences in 2% and 10% BSM macrorheology, whereas in the absence of evaporation control 10% BSM demonstrated a significantly higher viscoelasticity at 37 °C. Similarly, during the measurements without evaporation control at 37 °C we observed a substantial increase in the storage modulus G’ and the loss modulus G’’ of the highly viscoelastic CF sputum but not in the healthy sputum. Conclusion: Our data show that integration of a solvent trap preventing evaporation is essential for macrorheological analysis of mucus model systems and native human sputum, especially for measurements of highly viscoelastic samples at physiological temperature of 37 °C. This optimized protocol will facilitate standardized quantitative assessment of abnormalities in viscoelastic properties of airway mucus and response to muco-active therapies in patients with CF and other muco-obstructive lung diseases.